The moderating effects of family and state ownership on value relevance of accounting information in Malaysia - Mirza, Aboubakar (2019)
Firm value represents the economic worth of a firm. It is a good indicator of investor perception about a firm’s prospect. Many factors influence firm value; one of the most influencing factors is accounting information. Therefore, unbiased accounting information is of the utmost importance. Otherwise, it will be considered irrelevant for decision-making by investors and will result in lower value relevance (firm value) of accounting information. The primary accounting information earning is losing value relevance due to the managerial manipulation practices by the Malaysian listed firms. Investors are now relying more on other accounting information for decision-making. According to agency theory, concentrated ownership is the most significant factor that determines the value relevance of accounting information. The value relevance research has paid more attention to concentrated ownership and overlooked the unique agency context of concentrated family and state ownership, a common phenomenon in Malaysia. Therefore, this study investigates value relevance of earning, book value of equity, and cash flow from operations. Due to inconsistencies in prior studies, the moderating role of family and state-ownership on the value relevance of earning, book value of equity, and cash flow from operations are also examined. The sample of 607 public listed companies were used to test the hypotheses over the period 2012-2016. Using Prais-Winsten (PCSE) multivariate regression, this study finds that earning, book value of equity, and cash flow from operations are value relevant, and family ownership moderates the value relevance of earning, book value of equity, and cash flow from operations. State ownership only moderates the value relevance of book value of equity and cash flow from operations. These results have theoretical implications for the alignment and entrenchment hypotheses of the agency theory and practical implications for the regulators to improve investors’ perception regarding quality of accounting information.